Cannabis as a potential compound against various malignancies, legal aspects, advancement by exploiting nanotechnology and clinical trials. (9th August 2022) - Hasan, Nazeer; Imran, Mohammad; Sheikh, Afsana; Saad, Suma; Chaudhary, Gaurav; Jain, Gaurav Kumar; Kesharwani, Prashant; Ahmad, Farhan J.
Abstract: Various preclinical and clinical studies exhibited the potential of cannabis against various diseases, including cancer and related pain. Subsequently, many efforts have been made to establish and develop cannabis-related products and make them available as prescription products. Moreover, FDA has already approved some cannabis-related products, and more advancement in this aspect is still going on. However, the approved product of cannabis is in oral dosage form, which exerts various limitations to achieve maximum therapeutic effects. A considerable translation is on a hike to improve bioavailability, and ultimately, the therapeutic efficacy of cannabis by the employment of nanotechnology. Besides the well-known psychotropic effects of cannabis upon the use at high doses, literature has also shown the importance of cannabis and its constituents in minimising the lethality of cancer in the preclinical models. This review discusses the history of cannabis, its legal aspect, safety profile, the mechanism by which cannabis combats with cancer, and the advancement of clinical therapy by exploiting nanotechnology. A brief discussion related to the role of cannabinoid in various cancers has also been incorporated. Lastly, the information regarding completed and ongoing trials have also been elaborated.